Composición de aceite esencial de limón cáscara como promotor de crecimiento en la industria avícola - Rojas Duran, Rosario Elena (2013)
The invention relates to a composition of lemon peel essential oil useful as a growth promoter in poultry, said composition comprises at least 16.84 to 46.12 % d-limonene; 5.67 to 19.86 % y-terpinene; 4.27 to 12.13 % terpinolene; 4.60 to 14.75 % p-menth-l-3n-8-ol; among other components. The invention also relates to a food supplement for poultry, which comprises 1 kg per metric ton of feed of the said essential oil composition.